Visual–somatotopic interactions in spatial perception. Issue 3 (10th February 2016) - Samad, Majed; Shams, Ladan
Abstract : Ventriloquism is a well-studied multisensory illusion of audiovisual spatial perception in which the perceived location of an auditory stimulus is shifted in the direction of a synchronous, but spatially discrepant visual stimulus. This effect is because of vision's superior acuity in the spatial dimension, but has also been shown to be influenced by the perception of unity of the two signals. We sought to investigate whether a similar phenomenon may occur between vision and somatosensation along the surface of the body as vision is known to possess superior spatial acuity to somatosensation. We report the first demonstration of the visuotactile ventriloquist illusion: individuals were instructed to localize visual stimuli (small white disks) or tactile stimuli (brief localized vibrations) that were presented concurrently or individually along the surface of the forearm, where bimodal presentations included spatially congruent and incongruent stimuli. Participants showed strong visual–tactile interactions. The tactile localization was strongly biased in the direction of the visual stimulus and the magnitude of this bias decreased as the spatial disparity between the two stimuli increased. The Bayesian causal inference model that has previously been shown to account for auditory–visual spatial localization and the ventriloquism effect also accounted well for the present data. Therefore, crossmodal interactions involving spatial representation along the surface of the body follow the same rules as crossmodal interactions involving representations of external space (auditory–visual).